All through the Town The School Bus as Educational Technology - Garcia, Antero (Forerunners: Ideas First, 2023)
p strongThe role of the humble school bus in transforming education in America/strong Everyone knows the yellow school bus. It's been invisible and also omnipresent for a century. Antero Garcia shows how the U.S. school bus, its form unaltered for decades, is the most substantial piece of educational technology to ever shape how schools operate. As it noisily moves young people across the country every day, the bus offers the opportunity for a necessary reexamination of what "counts" as educational technology. Particularly in light of these buses being idled in pandemic times, emAll through the Town/em questions what we take for granted and what we overlook in public schooling in America, pushing for liberatory approaches to education that extend beyond notions of school equity. emForerunners: Ideas First/em is a thought-in-process series of breakthrough digital publications. Written between fresh ideas and finished books, Forerunners draws on scholarly work initiated in notable blogs, social media, conference plenaries, journal articles, and the synergy of academic exchange. This is gray literature publishing: where intense thinking, change, and speculation take place in scholarship./p